Ages and metallicities of five intermediate-age star clusters projected towards the Small Magellanic Cloud - Piatti, Andres Eduardo (2001)
Colour–magnitude diagrams are presented for the first time for L32, L38, K28 (L43), K44 (L68) and L116, which are clusters projected on to the outer parts of the Small Magellanic Cloud (SMC). The photometry was carried out in the Washington system C and T1 filters, allowing the determination of ages by means of the magnitude difference between the red giant clump and the main-sequence turn-off, and metallicities from the red giant branch locus. The clusters have ages in the range 2–6 Gyr, and metallicities in the range −1.65<[Fe/H]<−1.10, increasing the sample of intermediate-age clusters in the SMC. L116, the outermost cluster projected on to the SMC, is a foreground cluster, and somewhat closer to us than the Large Magellanic Cloud. Our results, combined with those for other clusters in the literature, show epochs of sudden chemical enrichment in the age–metallicity plane, which favour a bursting star formation history as opposed to a continuous one for the SMC.